Iron-Catalyzed Benzene Ring Expansion of α-Azido-N-phenylamides - Wei, Kaijie; Jiang, Menglu; Liang, Siyu; Yu, Wei (Synthesis, 2022)
Nitrenoid-mediated C–H insertion and cycloaddition reactions are gaining increasing importance in modern organic synthesis. However, the nitrene-mediated benzene ring expansion, which constitutes a potent tool for breaking the benzene ring, has sparely been explored for synthetic purposes. Herein we report that nitrene cycloaddition to the benzene ring can be enabled intramolecularly by iron catalysis. By using FeCl2 and N-heterocyclic carbene SIPr·HCl as the catalyst, α-azido-N-phenylamides can be converted into 1,3-dihydro-2H-azepin-2-ones in good yields through a novel skeleton rearrangement. The rearrangement features a cascade of nitrene cycloaddition, C–N cleavage, water addition, and electrocyclic ring-opening. In the case that the N-phenyl ring is substituted with a methoxy group at the meta or para position, azepin-2-one-fused imidazolinones can also be obtained. The present reactions provide an effective method for benzene ring expansion as well as for the preparation of azepin-2-one compounds.
Keywords: azides; azepin-2-one; cycloaddition; iron catalysis; nitrene; phenyl migration; ring expansion